On ditching the watch while training: Re-examining the pace-based approach to training long-distance runners - Whitehead, P. M. (The Sport Journal, 2016)
This paper presents two arguments against the pace-based approach to running, defined as the reduction of training intensity to measures of distance/time (that is, pace). The experimental data of Daniels (5) is presented as an example of this. It is argued that the pace-based approach ignores many variables that are important in understanding the physiology and psychology of training long distance runners. The first argument examines the assumption that pace may be used as a general approximation of intensity. This ignores the role of confounding environmental factors like altitude, temperature, and wind. The second argument examines the assumption that any measure of intensity is as good as or better than another. Heart rate, blood-lactate levels, and volume of oxygen consumption are physiological markers that provide useful information for understanding levels of intensity, but their relationship is not certain.